The features of magnetoresistance of n-Si doped with phosphorus from the melt and by nuclear transmutation - Baranskii, P.I.; Babich, V.M.; Venger, E.F.; Dotsenko, Yu.P. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2000)
The magnetic field dependencies Dr^/r0 = f(H) were investigated for phosphorus-doped n-Si crystals at a temperature of 77.4 K in classical strong magnetic fields up to 200 kOe. We revealed and discuss some distinctions in the field dependencies of magnetoresistance for crystals doped from melt and those doped by nuclear transmutation. It is shown that mag-netoresistance ∆ρ⊥/ρ₀ in classical strong magnetic fields is due to the statistically distributed Herring-type defects in the crystals studied.